Proteomics analysis of rough endoplasmic reticulum in pancreatic beta cells. Issue 9 (May 2015) - Lee, Jin‐sook; Wu, Yanning; Schnepp, Patricia; Fang, Jingye; Zhang, Xuebao; Karnovsky, Alla; Woods, James; Stemmer, Paul M.; Liu, Ming; Zhang, Kezhong; Chen, Xuequn
Abstract : Pancreatic beta cells have well‐developed ER to accommodate for the massive production and secretion of insulin. ER homeostasis is vital for normal beta cell function. Perturbation of ER homeostasis contributes to beta cell dysfunction in both type 1 and type 2 diabetes. To systematically identify the molecular machinery responsible for proinsulin biogenesis and maintenance of beta cell ER homeostasis, a widely used mouse pancreatic beta cell line, MIN6 cell was used to purify rough ER. Two different purification schemes were utilized. In each experiment, the ER pellets were solubilized and analyzed by 1D SDS‐PAGE coupled with HPLC‐MS/MS. A total of 1467 proteins were identified in three experiments with ≥95% confidence, among which 1117 proteins were found in at least two separate experiments and 737 proteins found in all three experiments. GO analysis revealed a comprehensive profile of known and novel players responsible for proinsulin biogenesis and ER homeostasis. Further bioinformatics analysis also identified potential beta cell specific ER proteins as well as ER proteins present in the risk genetic loci of type 2 diabetes. This dataset defines a molecular environment in the ER for proinsulin synthesis, folding and export and laid a solid foundation for further characterizations of altered ER homeostasis under diabetes‐causing conditions. All MS data have been deposited in the ProteomeXchange with identifier PXD001081 (http://proteomecentral.proteomexchange.org/dataset/PXD001081 ).